Using the distributive property, Marta multiplied the binomial (2x + 3) by the trinomial (x2 + x – 2) and got the expression below.

(2x)(x2) + (2x)(x) + (2x)(–2) + (3)(x2) + (3)(x) + (3)(–2)

Which is the simplified product?

2x3 + 6x2 – x – 6
2x3 + x2 – x – 6
2x3 + 5x2 – x – 6
2x3 – x2 – 7x – 6

Respuesta :

frika

Marta got the expression

[tex]2x\cdot x^2 + 2x\cdot x + 2x\cdot (-2) + 3\cdot x^2 + 3\cdot x + 3\cdot (-2).[/tex]

First, note that

[tex]2x\cdot x^2=2x^3,\\2x\cdot x=2x^2,\\2x\cdot (-2)=-4x,\\3\cdot x^2=3x^2,\\ 3\cdot x=3x,\\3\cdot (-2)=-6.[/tex]

Then add terms with the same degree:

[tex]2x^2+3x^2=5x^2,\\-4x+3x=-x.[/tex]

At last,

[tex](2x+3)(x^2 + x - 2)=2x^3+5x^2-x-6.[/tex]

Answer: correct choice is C.

aksnkj

The resultant product of the given polynomials is [tex]2x^3+5x^2-x-6[/tex]. Option C is correct.

Given information:

Using the distributive property, Marta multiplied the binomial (2x + 3) by the trinomial [tex](x^2 + x - 2)[/tex].

The resultant of the above product is [tex](2x)(x^2) + (2x)(x) + (2x)(-2) + (3)(x^2) + (3)(x) + (3)(-2)[/tex].

Solve the given product as,

[tex](2x+3)(x^2+x-2)=(2x)(x^2) + (2x)(x) + (2x)(-2) + (3)(x^2) + (3)(x) + (3)(-2)\\=2x^3+2x^2-4x+3x^2+3x-6\\=2x^3+5x^2-x-6[/tex]

Therefore, the resultant product of the given polynomials is [tex]2x^3+5x^2-x-6[/tex]. Option C is correct.

For more details, refer to the link:

https://brainly.com/question/23675883